'A disastrous blow': psychiatric risk, social indicators and medical authority in abortion reform in post-war Britain. Issue 2 (30th May 2019) - Crook, Sarah
Abstract : The Second World War lent impetus to the creation of new models and explanatory frameworks of risk, encouraging a closer reading of the relationship between individual psychiatric disorder and social disarray. This article interrogates how conceptions of psychiatric risk were animated in debates around abortion reform to forge new connections between social conditions and psychiatric vulnerability in post-war Britain. Drawing upon the arguments that played out between medical practitioners, I suggest that abortion reform, culminating in the 1967 Abortion Act, was both a response to and a stimulus for new ideas about the interaction between social aetiologies and medical pathologies; indeed, it became a site in which the medical and social domains were recognised as mutually constitutive. Positioned in a landscape in which medical professionals were seeking to assert their authority and to defend their areas of practice, abortion reform offered new opportunities for medical professionals to intervene in the social sphere under the guise of risk to women's mental health. The debate in medical journals around the status of issues that were seen to bridge the social and the medical were entangled with increasing anxiety about patient agency and responsibility. These concerns were further underscored as conversations about psychiatric risk extended towards considerations of the potential impact on women's existing families, bringing domestic conditions and the perceived psychosocial importance of family life into relief within medical journals. This article, then, argues that conceptions of psychiatric risk, as refracted through the creation of new synapses connecting the social and the medical domains, were critical to medical debates over abortion reform in post-war Britain.